DETEKSI DINI KEBERADAAN SERANGGA HAMA PENTING PADA TANAMAN JAGUNG DI DESA MURUONA, KECAMATAN ILE APE, KABUPATEN LEMBATA - Yasinta L. Kleden; Rika Ludji; Gregoriana H. Koten (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This study aimed to detect the presence of key insect pests on corn in Muruona Village, Ile Ape Sub District, Lembata District in East Nusa Tenggara. This research was conducted from November 2020 to January 2021 on farmer's land in the region. This study used a survey method with direct observation techniques on corn plants, and sampling was carried out using sweep nets and sticky traps. The data collected included types of key insect pests, symptoms of damage, population, and intensity of damage to corn by important insect pests. The results showed three key insect pests on corn plantation in the study area: Locusta migratoria, Ostrinia furnacalis, and Helicoverpa armigera. This key pests were detected in corn from the early vegetative to the generative period. The symptoms of damage on corn caused by Locusta migratoria, Ostrinia furnacalis, and Helicoverpa armigera occurred six days after planting (DAP), 28 DAP, and 56 DAP, respectively. Symptoms of damage to corn plants caused by Locusta migratoria are tears in the leaves resembling serrations on the edges of the leaves, both young and old. Symptoms of damage to corn plants caused by Ostrinia furnacalis are grinding holes on the stems so that the stems so that the stem become damaged and then break. Grinding marks on the cobs and dirt and grinding powder characterize symptoms of damage to corn plants caused by Helicoverpa armigera. Populations of the key insect pests Locusta migratoria, Ostrinia furnacalis, and Helicoverpa armigera were very small, with 4, 3 and 1 insect, respectively. Moreover, for the highest intensity of damage to corn plants was caused by Ostrinia furnacalis, but it was categorized as light damage intensity because it was > 0 % ≤ 25%.